Low miR200b-5p levels in minor salivary glands: a novel molecular marker predicting lymphoma development in patients with Sjögren's syndrome. Issue 8 (19th May 2018) - Kapsogeorgou, Efstathia K; Papageorgiou, Aristea; Protogerou, Athanase D; Voulgarelis, Michael; Tzioufas, Athanasios G
Abstract : Objectives: Development of non-Hodgkin's lymphoma (NHL) is the major adverse outcome of Sjögren's syndrome (SS) affecting both morbidity and mortality. Preliminary evidence suggested that, although not deregulated compared with sicca controls, miR200b-5p levels are decreased in the minor salivary glands (MSGs) of SS patients with NHL. The aim of the current study was to evaluate the MSG expression of miR200b-5p in SS-associated NHLs and its potential predictive value for the identification of patients with SS susceptible to develop NHL. Methods: miR200b-5p expression was investigated in MSG tissues of patients with SS who were at: (A) low risk and did not develop NHL during follow-up (n=27; median follow-up time on biopsy performance, range: 8.9 years, 1.33–14 years), (B) high-risk and diagnosed with NHL during follow-up (prelymphoma; n=17; median follow-up to until lymphoma diagnosis, range: 3.67 years, 0.42–8.5 years) and (C) had NHL (n=35), as well as non-SS sialadenitis controls (sarcoidosis and hepatitis C virus (HCV) infection, four each). The differential miR200b-5p expression, correlations with disease features and its discriminative/predictive value, was evaluated by appropriate statistical approaches. Results: The MSG levels of miR200b-5p were significantly downregulated in patients with SS who will develop or have NHL and strongly discriminated (p<0.0001) them from those without lymphoma or non-SS sialadenitis. Furthermore, they were reduced long before clinical onset of lymphoma, did not significantly change on transition to lymphoma and, importantly, were proved strong independent predictors of patients who will develop NHL (p<0.0001). Conclusions: These findings support that miR200b-5p levels in MSGs represent a novel predictive and possibly pathogenetic mechanism-related factor for the development of SS-associated NHL, since its expression is impaired years before lymphoma clinical onset.